A common SCN1A splice‐site polymorphism modifies the effect of carbamazepine on cortical excitability—A pharmacogenetic transcranial magnetic stimulation study. Issue 2 (13th January 2014) - Menzler, Katja; Hermsen, Anke; Balkenhol, Katharina; Duddek, Caroline; Bugiel, Hannes; Bauer, Sebastian; Schorge, Stephanie; Reif, Philipp S.; Klein, Karl Martin; Haag, Anja; Oertel, Wolfgang H.; Hamer, Hajo M.; et al.
Summary Objective SCN1A encodes the alpha subunit of the voltage‐gated sodium channel and plays a crucial role in several epilepsy syndromes. The common SCN1A splice‐site polymorphism rs3812718 (IVS5N+5 G>A) might contribute to the pathophysiology underlying genetic generalized epilepsies and is associated with electrophysiologic properties of the channel and the effect of sodium‐channel blocking antiepileptic drugs. We assessed the effects of the rs3812718 genotype on cortical excitability at baseline and after administration of carbamazepine in order to investigate the mechanism of this association. Methods Paired‐pulse transcranial magnetic stimulation (TMS) was applied in 92 healthy volunteers with the homozygous genotypes AA or GG of rs3812718 at baseline and after application of 400 mg of carbamazepine or placebo in a double‐blind, randomized, crossover design. Resting motor threshold (RMT), short interval intracortical inhibition (SICI), intracortical facilitation (ICF), and cortical silent period (CSP) were determined. Results At baseline there was no significant difference in any TMS parameter. Genotype GG was associated with a higher carbamazepine‐induced increase in CSP duration as compared to AA (multivariate analysis of covariance [MANCOVA], p = 0.013). An expected significant increase in RMT was genotype independent. Significance We found that the rs3812718 genotype modifies the effect of carbamazepine on CSP duration (mainly reflecting modulation of γ‐aminobutyric acid (GABA)ergic inhibition), but not on RMT (mainly reflecting modulation of voltage‐gated sodium channels). This provides evidence that rs3812718 affects the pharmacoresponse to carbamazepine via an effect on GABAergic cortical interneurons. Our results also confirm that TMS is useful to investigate the effect of genetic variants on cortical excitability and pharmacoresponse.